Thematic analysis as a type of discourse analysis: synthesis of sociological and linguistic approaches - Turkina, Aksana A. (Journal of the Belarusian State University. Philology, 2019)
The article focuses attention on the actual for linguistic discourse methodology – a thematic analysis, born in the course of sociological research and adapted for linguistic tasks. The article describes and demonstrates how this kind of analysis helps to reconstruct the subject-oriented (reference) content of specific discourses (texts with contextual information inscribed in them), namely, how to reconstruct cognitive, pragmatic, paradigmatic and syntagmatic structure of macrotext space. The article describes the procedure of in-depth thematic analysis, in which the thematic analysis of qualitative sociology is integrated, a dialogue-performative analysis of narrative studies, methods for reconstructing discourse pictures of the world and discourse-portraits of addressees in the context of the functioning of discourses. The method includes a number of private techniques and techniques for the collection and organization of a database, description, verification, theoretical modeling. A step-by-step study of the verbal series involves identifying topics with an explicit and implicit representation. In this connection, the abduction method is significant, which precedes the transition from inductive collection of information to the deductive and back. The article describes the specifics of conducting a thematic analysis in a linguistic study on the example of an individual case: the discourse of the winner of the first issue of the Russian-language reality show «The Survivor – 1».